Menggagas Agama Baru di Era Postmodernisme - Muhammad Zain (Ulumuna, 2005)
When man has come to the highest level of achievement of the use of ratio, well known as postmodern era, religion is still believed to be the solution of humanistic problems. Even in the ultimate level of the use of ratio, religion becomes an expectation. This expectation will never be a reality unless religion can play its part in our every day life. Religion nowadays is understood formally, partially and exclusively. This makes it hard for the religion to cope with the ongoing problems encountered by human beings. To make thing worse, this understanding even can lead to a more severe condition where religion is blamed to be the cause of some social chaos, riots, violence, oppression and injustice. Therefore, to make the dream comes true, religion should be able to play its role universally, as the characteristics of its values. Moreover, if it is believed that a religion comes from the Al-Mighty God, the God of all universes, the values and teachings of the religion are values that go into effects to the whole humankind.